READING COMPREHENSION EXERCISES ONLINE: THE EFFECTS OF FEEDBACK, PROFICIENCY AND INTERACTION - Philip Murphy (Language Learning and Technology, 2007)
This paper describes an ongoing project to create an online version of a reading programme, a custom-designed English language proficiency course at a university in Japan. Following an interactionist view of second language acquisition, it was hypothesised that comprehension of a reading passage could be enhanced by online materials promoting interaction between students as they completed a multiple-choice reading comprehension exercise. Interaction was promoted: (a) through pair work at a single computer and (b) by providing Elaborative feedback in the form of hints about incorrect answers as a means of stimulating discussion about corrections. Students were randomly selected from upper and lower levels of English proficiency, as determined by the Kanda English Proficiency Test (Bonk & Ockey, 2003), to receive either Elaborative feedback or Knowledge of Correct Response feedback (which supplies the correct answers). Within these groups, some students worked in pairs and some alone. Quantitative results show that the interaction between Type of feedback and Manner of study (individual or pair work) was statistically significant; students performed best on a follow-up comprehension exercise when in pairs and having been provided with Elaborative feedback. Furthermore, qualitative analysis of transcribed interactions also shows that Elaborative feedback was conducive to quality interaction.